In vitro allelopathic potential of Leonurus sibiricus L. leaves - Rolim de Almeida, Luiz Fernando [UNESP]; Delachiave, Maria Elena [UNESP]; Sannomiya, Miriam [UNESP]; Vilegas, Wagner [UNESP]; dos Santos, Lourdes Campaner [UNESP]; Mancini, Emilia; De Feo, Vincenzo (Taylor & Francis Ltd, 2008)
The chemical interaction between plants is known as allelopathy and it is related to the release of substances into the environment. The present study aimed at the evaluation of the allelopathic activity of the leaves of Leonurus sibiricus against the germination and initial growth of Raphanus sativus, Lactuca sativa, and Lepidium sativum. Chemical analyses showed the presence in the leaves of four major flavonoids (quercetin-3-O-alpha-L-rhamnopyranosyl-(1 > 6)-beta-D-galactopyranoside; rutin; hyperin, and isoquercetrin) and of three minor flavonoidic compounds (genkwanin, 3'-hydroxy genkwanin, and quercetin). Extracts, their chromatographic fractions and pure isolated flavonoids showed different biological activities. A methanol extract of leaves of Leonurus sibiricus caused significant reduction only in the germination of Lactuca sativa, with no effects on the germinative processes of Raphanus sativus and Lepidium sativum. Some chromatographic fractions, containing the flavonoids, showed inhibitory activity on the initial stages of root growth of all tested seeds. The isolated flavonoids, at the higher concentration tested (10(-4) M) seemed to be responsible for the inhibition of the germination, as well as the radical elongation. Among pure compounds, 3'-OH-genkwanin and quercetin showed the stronger antigerminative activity at the concentration of 10(-4) M, whereas the radical elongation was reduced by rutin, isoquercetrin and 3'-OH-genkwanin. All compounds, tested at concentrations ranging between 10(-5) and 10(-7) M, showed stimulatory activities.
Keywords: Leonurus sibiricus; flavonoids; in vitro allelopathic activity